Mesenchymal stem cells for inflammatory airway disorders: promises and challenges. Issue 1 (30th January 2019) - Fan, Xing-Liang; Zhang, Zhao; Ma, Chui Yan; Fu, Qing-Ling
Abstract : The regenerative and immunomodulatory characteristics of mesenchymal stem cells (MSCs) make them attractive in the treatment of many diseases. Although they have shown promising preclinical studies of immunomodulation and paracrine effects in inflammatory airway disorders and other lung diseases, there are still challenges that have to be overcome before MSCs can be safely, effectively, and routinely applied in the clinical setting. A good understanding of the roles and mechanisms of the MSC immunomodulatory effects will benefit the application of MSC-based clinical therapy. In this review, we summarize the promises and challenges of the preclinical and clinical trials of MSC therapies, aiming to better understand the role that MSCs play in attempt to treat inflammatory airway disorders.